Divalent Metal Uptake and the Role of ZIP8 in Host Defense Against Pathogens - Samuelson, Derrick R.; Haq, Sabah; Knoell, Daren L. (Frontiers in Cell and Developmental Biology, 2022)
Manganese (Mn) and Zinc (Zn) are essential micronutrients whose concentration and location within cells are tightly regulated at the onset of infection. Two families of Zn transporters (ZIPs and ZnTs) are largely responsible for regulation of cytosolic Zn levels and to a certain extent, Mn levels, although much less is known regarding Mn. The capacity of pathogens to persevere also depends on access to micronutrients, yet a fundamental gap in knowledge remains regarding the importance of metal exchange at the host interface, often referred to as nutritional immunity. ZIP8, one of 14 ZIPs, is a pivotal importer of both Zn and Mn, yet much remains to be known. Dietary Zn deficiency is common and commonly occurring polymorphic variants of ZIP8 that decrease cellular metal acquisition (Zn and Mn), are associated with increased susceptibility to infection. Strikingly, ZIP8 is the only Zn transporter that is highly induced following bacterial exposure in key immune cells involved with host defense against leading pathogens. We postulate that mobilization of Zn and Mn into key cells orchestrates the innate immune response through regulation of fundamental defense mechanisms that include phagocytosis, signal transduction, and production of soluble host defense factors including cytokines and chemokines. New evidence also suggests that host metal acquisition may have long-term consequences by influencing the adaptive immune response. Given that activation of ZIP8 expression by pathogens has been shown to influence parenchymal, myeloid, and lymphoid cells, the impact applies to all mucosal surfaces and tissue compartments that are vulnerable to infection. We also predict that perturbations in metal homeostasis, either genetic- or dietary-induced, has the potential to impact bacterial communities in the host thereby adversely impacting microbiome composition. This review will focus on Zn and Mn transport via ZIP8, and how this vital metal transporter serves as a “go to” conductor of metal acquisition that bolsters host defense against pathogens. We will also leverage past studies to underscore areas for future research to better understand the Zn-, Mn- and ZIP8-dependent host response to infection to foster new micronutrient-based intervention strategies to improve our ability to prevent or treat commonly occurring infectious disease.